The Microbiome and Cancer Unveiling the Microbe-Tumor Crosstalk - Singamayum Ashif (African Journal of Environmental Economics and Management, 2025)
With more and more evidence showing that gut microbiota significantly affects tumour biology, the complex relationship between the human microbiome and cancer has attracted a lot of attention. The aim of this study is to introduce an innovative theoretical framework that integrates information from microbiology, immunology, oncology, and bioinformatics in order to enhance our under- standing of the interactions between microorganisms and tumours. The introduction provides a thorough summary of the human microbiome while highlighting the important role it plays in the development of pathogenic disorders. Moreover, it offers a succinct overview of key concepts in cancer biology, emphasising the significance of examining the relationship between the microbiome and illnesses associated with cancer. An exhaustive literature analysis compiles the foremost discoveries about the impact of the microbiome on cancer. It provides an explanation of how mechanisms such as metabolic relationships, immunological regulation, and inflammatory pathways function. Lastly, it highlights the deficiencies in existing research that necessitate the implementation of more comprehensive methods. The results show that the gut microbiota may affect the growth of tumours in certain ways, such as by changing the immune system, signalling pathways, and bacterial products. Methodological approaches encompass a thorough examination of existing literature, the integration of fundamental ideas, and the creation of a comprehensive model that visually represents these intricate relationships. We evaluate the framework's accuracy by generating predicted scenarios and analyzing the possible consequences for clinical practice and research. We propose new diagnostic indicators and therapeutic techniques that specifically target the microbiome.